Effect of mutual coupling on spatial correlation for different manifold arrays - Ying YANG; Weidong LI; Cuiwei XUE; Qiuming ZHU; Zhizhong LIAO; Xiaomin CHEN (Dianxin kexue)
The mechanism of MC and its impact on the received signal vector were analyzed.A closed-form expression and an approximate expression of SC for antenna arrays with different forms were derived,where the power angle spectrum of arrival signal was modeled as Von Mises (VM) distribution.On this basis,the general expressions of SC with MC effect was derived.Simulation results show that the proposed analytical expressions are in good agreement with the numerical integration results.In addition,under the mutual coupling effect,the correlation of antenna array elements fluctuates around the correlation curve without mutual coupling,and the planar array has better resistance to mutual coupling.